Antibacterial efficacy of rifampin loaded solid lipid nanoparticles against Staphylococcus epidermidis biofilm. (April 2016) - Fazly Bazzaz, Bibi Sedigheh; Khameneh, Bahman; Zarei, Hamed; Golmohammadzadeh, Shiva
Abstract: Objective: The aim of the present study was to assess the in vitro anti-biofilm activities of solid lipid nanoparticles (SLN) loaded with rifampin against biofilm-producing Staphylococcus epidermidis . Methods: SLN were prepared and characterized for size, zeta potentials and encapsulation efficacy. The morphological and thermal properties of formulation were evaluated by TEM imagining and DSC analysis. The anti-biofilm activity of different formulations was assessed at different incubation times and concentrations by crystal violet (CV) and viable biofilm count methods. Results: The zeta potentials, particle sizes and encapsulation efficiencies of final formulations were 17 ± 0.7 mV, 101 ± 4.7 nm and approximately 70%; respectively. Rifampin-SLN was able to reduce the biomass of biofilm at time- and concentration-dependent manner. According to biofilm count results, the Rifampin-SLN was more effective for removal of the bacteria with respect to free rifampin. Conclusion: The results of this study highlight the advantages and efficiency of Rifampin-SLN in biofilm eradication. Highlights: The final SLN formulations showed sufficient physicochemical properties and were able to deliver rifampin to biofilm. Rifampin-SLN was more efficient in biofilm degradation and also killing bacteria in comparison with free rifampin. The results highlighted the advantages and efficiency of SLN in biofilm eradication.